A new subspecies of Passiflora lobbii (Passifloraceae) from the western slope of the peruvian Andes - Chávez Corcuera, Gonzalo Fernando (2021)
Passiflora lobbii subsp. limensis Chávez-Corcuera is described. It differs from the other subspecies of Passiflora lobbii by presenting two ocelli on the abaxial side of the lamina, petioles with two glands located in its middle zone and larger leaf blades. Additionally, a key for determination of the related taxa and a table with morphological characters of the leaves of subspecies of Passiflora lobbii are presented.